Pelatihan dan pendampingan budidaya maggot sebagai pupuk organik dan pakan ternak di desa Jelu - Elvania, Nindy Callista; Cahyan, Angelia; Safitri, Milanda; Haryono, Aldi; Prayogo, Cendi Ahmad; Pramudya, Tio Gergia Rangga; Astutik, Sri Wahyu Vidiya (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Jelu Village in Bojonegoro Regency has great agricultural potential but faces challenges in managing organic waste and providing quality animal feed. The Thematic KKN Program Group 04 of Bojonegoro University (KKN-TK 04 Unigoro) designed training and mentoring activities on maggot cultivation (Black Soldier Fly Larvae) to address these issues. This community service activity aims to evaluate the effectiveness of the training and mentoring in improving residents' knowledge and skills in maggot cultivation, as well as its impact on the production of organic fertilizer and animal feed. The methods used include preparation, socialization, technical training, and implementation mentoring. The results of the community service showed a significant increase in the residents' understanding and skills regarding maggot cultivation. The community also learned that adult maggot larvae can be used as a source of high-quality animal feed. In addition, this program successfully increased residents' awareness of the importance of sustainable organic waste management.